Pelatihan Pembuatan Database Menggunakan Microsoft Excel 2010 bagi Perangkat Desa Salakan - Rahayu, Cicilia Puji (Fakultas Ekonomi Universitas Surakarta, 2024)
Abstract The village government is the lowest level of government in the government structure, so it is mandatory to provide valid basic data as a source of information in government institutions. Based on this, the village government should have prepared a population database that is systematic and well-stored. However, it is undeniable that not all villages in Indonesia have a population database that is well-organized, including in Salakan Village at that time. When the community service team first coordinated with the Head of Salakan Village, information was obtained that the population data storage owned by Salakan Village had been computerized with ordinary Microsoft Excel, but had not been made systematically due to the limited capabilities of village officials regarding the Microsoft Excel application. This motivated the community service team to provide additional insight that the population data storage that was already owned could be improved into systematic data. The improvement was carried out through training in creating a database using Microsoft Excel 2010 for the Salakan Village apparatus on Saturday, July 11, 2020. The results of this training, the participants have understood that population data can be created systematically by creating a database using Microsoft Excel 2010, and most of the participants have also succeeded in practicing it. Keywords : database, Microsoft Excel 2010, Salakan Village